SISI FILOSOFIS AL-QUR’AN: BEBERAPA KISAH ILUSTRATIF - Aris Widodo (UIN K.H. Abdurrahman Wahid Pekalongan, 2010)
Quran is a guide book that is able to accommodate many human beings’s thought levels. By special language style, it can also be viewed from various fields like law, theology, philosophy, and tasawuf related to reviewer’s preference. Therefore, Quran, in fact, can also be a starting point for philosophical study because it gives various materials to philosophical contemplations. This paper gives illustration of how the Quran with its stories in it is able to arouse our philosophical sensitivities. By referring to six branches of philosophy i.e. logic, epistemology, cosmology, metaphysic, ethic, and esthetic, this paper tries to show that the Quran in certain aspect can be claimed by us to have philosophical side.